1981
DOI: 10.1515/zna-1981-0313
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Zero Field Splittings and Site Distortions III. MnBr4 2- and Crystal Structure Refinements for Rb3ZnBr5 and Cs2ZnBr4

Abstract: C o r r e la tio n o f Z e ro F ield S p littin g s a n d S ite D is to r tio n s III . M n B r42~ a n d C r y s ta l S tr u c tu r e R e fin e m e n ts f o r R b 3Z n B r 5 a n d C s g Z n BM. Heming and G. Lehmann Institut für Physikalische Chemie, Westfälische Wilhems-Universität, Münster and G. Henkel and B. Krebs Institut für Anorganische Chemie, Westfälische Wilhelms-Universität, Münster Z. Naturforsch. 36a, 286-293 (1981); received January 31, 1980 EPR data for Mn2+ in Cs2ZnBr4, Rb3ZnBr5, Cs3CdBr5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The high sensitivity of our treatment to the distortions is confirmed by the distortion diagrams, introduced in Ref. [18], from which we obtain the values of Tab. 6, to be compared with the experimental values given in Tabs.…”
Section: S1supporting
confidence: 61%
“…The high sensitivity of our treatment to the distortions is confirmed by the distortion diagrams, introduced in Ref. [18], from which we obtain the values of Tab. 6, to be compared with the experimental values given in Tabs.…”
Section: S1supporting
confidence: 61%
“…Alternatively, the methods of distortion diagrams introduced in [8] showed that the experimental data could not be fitted with the assumption (2) for the parameters, when the Gd3+ ion was displaced.…”
Section: Atommentioning
confidence: 99%
“…Second degree parameters (units of 10~4cm_1) and direction of the crystal field principal axis for selected values of the Gd3+ in plane displacements. They are deduced from the distortion diagrams [8], using the two exponents power law with the parameters (2). Table 5.…”
Section: Atommentioning
confidence: 99%
“…For the meaning of the numbers on the ordinate see Figure 2. Since this is a rotation from v to x, the experimental curve in this case is given by -(b 2 + cos 2 <p • bt)/lb 2 where <p is the angle to the b (the magnetic y) axis. responsible.…”
Section: Discussionmentioning
confidence: 99%
“…The orientations of the a-and b-axes in the plane of the layers were determined by X-ray precession photographs. EPR measurements were performed on a commercial Q-band spectrometer at room temperature, details of the experimental procedure and the evaluation of numerical data were previously reported [2], [10]. Since the crystals are sensitive against humidity and air, they were handled in a glove box under dry nitrogen and were completely covered with the glue UHU-hart (UHU-Vertrieb GmbH, D-7580 Bühl) during the measurements.…”
Section: Methodsmentioning
confidence: 99%